Age does not equal: religion and gender in older adults of the northeast of Mexico - Acevedo Alemán, Jesús (2014)
Religiosity and gender currently represent two major challenges for scholars of the issue of ageing, so this document is intended to expose the results in relation to the conditions of life in which the adults elderly of the city of Saltillo, Coahuila, Mexico are such factors and how are related. The study considered a sample of 1,500 people over the age of 65. According to the results of the investigation it was concluded that the aging process and the variables that are part of this process are elements that are influenced by the gender and religiosity, therefore their traditional role in your family affects the way is given the coping with everyday life in aging and hence the importance of the contrast of these results with the roles both individual with the family as a whole.